Design of the AGV Trolley for Transporting the Drip Irrigation Belt Roll. Issue 1 (March 2021) - Meng, Fanzhao; Wei, Daifeng
Abstract: Automatic Guided Vehicle (AGV) is a kind of driverless transport vehicle which can carry, store, and load and unload goods. It can follow the preset path, complete the task, and has the functions of obstacle avoidance and safety protection, which is widely used in automatic production system. This paper introduces the design and development of AGV trolley to realize the automatic production transformation of drip irrigation belt production line for agricultural irrigation. According to the design requirements of the drip irrigation belt rolling AGV trolley for the transformation of the production line, based on the previous design experience and technology of the automatic guided trolley, from the actual needs of engineering application, combined with the path guidance technology, embedded control system, sensor detection technology, module control and system control management technology, a tape guided AGV trolley with lifting module is designed, which realizes the functions of rolling, transporting and storing of drip irrigation belt, and the production efficiency of drip irrigation belt is improved.